Crisis Communication During Internal System Failures: Role of Guest Service Representatives in Hotels - Bandara, Kuruppu Gedara Ivoni Madubhashini (Auckland University of Technology, 2026)
In today's digital era, hotels around the world integrate complex technological systems to ensure operational efficiency and deliver seamless guest experiences. However, relying heavily on technology makes them vulnerable to IT (Information Technology) breakdowns such as PMS (Property Management System) failures, POS (Point Of Sales) failures, key encoder failures, and key card malfunctions, all of which can increase critical operational risks and disrupt guest experiences. As front-line employees, guest service representatives (GSRs) are the first point of contact during internal operational disruptions due to technology failures. While existing hospitality research primarily focuses on external crises, business continuity planning, and managerial decision-making, limited attention has been given to GSRs, who act as both service professionals and immediate crisis responders during crisis events. This research aimed to address this gap by investigating how GSRs manage communication with guests during internal system failures. The study employs a qualitative methodology combining a document analysis and a netnographic analysis of online reviews posted on Booking.com and TripAdvisor platforms. To uncover recurring patterns and insights, the resultant data were analysed using thematic analysis. The findings revealed an absence of crisis communication frameworks of the organisation and protocols to guide GSRs in managing communication during internal system failures. By focusing on internal systems failures in hotels, this study contributes significantly to the existing literature on crisis communication in the hospitality industry, expanding the scope of crisis management research, which has previously focused mostly on external crises such as natural disasters, socio-economic crises, pandemics, and political instability. The study also offers valuable practical insights for hotel management to enhance their crisis communication practices by proposing concrete guidelines for communication protocols and thereby enabling GSRs to manage guest experiences and ensure improved service continuity during internal system failures.